Intangibles e inteligencia artificial: Una visión desde los derechos humanos en México - Montalvo Romero, María Teresa (2025)
The text examines the relationship between three key institutions: intellectual property, artificial intelligence, and human rights. In a legal context of state obligations, it discusses the protection of rights for individuals in Mexico, users of 4.0 technologies, and the legal uncertainty regarding the recognition of their intellectual creations. It explores the principles of intellectual property and its link to artificial intelligence, understood as the ability of machines to imitate human intelligence. Legal frameworks in Mexico and globally are discussed, linking them to human rights, concluding with the study of human control as an emerging but applicable right.